Pengaruh Overconfindence, Risk Tolerance dan Self Efficacy dalam Keputusan Investasi di Pasar Modal - Sesri Sellina; Erin Soleha (Otonomi, 2023)
For local and foreign investors, the capital market has become an attractive investment destination. The greater the interest of investors to invest in the capital market, the greater the buying and selling activity in the capital market, which can indicate that various business activities are running well. Making a decision to invest in the capital market does not only consider the fundamental aspects, but also considers the psychological aspects of investors. The purpose of this study was to determine the effect of overconfidence, risk tolerance and self-efficacy on investment decisions in the capital market. The population in this study is the z generation who are in the province of West Java, based on the slovin formula, a sample of 100 respondents is obtained. Sampling method using accidental sampling technique. Analysis method with the help of SmartPLS. The calculation results show that overconfidence has an effect on investment decisions in the capital market with a t-statistic value of 6.039, risk tolerance has an effect on investment decisions in the capital market with a t-statistic value of 3.586 and self-efficacy has an effect on investment decisions on the capital market with a t-statistic value of 2.330.